Perancangan Ulang Interior Le Dian Hotel & Cottages Di Kota Serang Dengan Pendekatan Aktivitas Bisnis - Nafis Khalaid, Nadiva; Firmansyah, Rangga; Sri Ismiranti, Athifa (Telkom University, 2024)
Le Dian Hotel & Cottages, a 4-star business hotel in Serang City, faces challenges in accommodating the needs of guests' business activities. This design aims to redesign the hotel interior with the approach of